Prenatal Testosterone Exposure Worsen the Reproductive Performance of Male Rat at Adulthood - Ramezani Tehrani, Fahimeh; Noroozzadeh, Mahsa; Zahediasl, Saleh; Ghasemi, Asghar; Piryaei, Abbas; Azizi, Fereidoun (PLOS ONE, 2013)
The reproductive system is extremely susceptible to environmental insults, for example exogenous steroids during gestational development and differentiation. Experimental induction of androgen excess during prenatal life in female animal models reprograms their reproductive physiology, however the fetal programming of the male reproductive system by androgen excess has not been well studied. We aimed to determine the effect of prenatal exposure of two different doses of testosterone on different gestational days, on the male reproductive system using a rat model. Sixteen pregnant rats were randomly divided into two experimental groups and two control groups. Experimental group І were subcutaneously injected with 3 mg free testosterone on gestational days 16-19 and its controls received solvent for that time; experimental group П were subcutaneously injected with 20 mg free testosterone on day 20 of gestational period and its controls received solvent at the same time. The reproductive system morphology and function of 32 male offspring of these study groups were compared at days 6-30-60 of age and after puberty. The anogenital distance of the male offspring of both experimental groups had no significant differences on the different days of measurement, compared with controls. In the offspring of experimental group І, the testes weight, number of Sertoli, Spermatocyte and Spermatid cells, sperm count and motility and the serum concentration of testosterone after puberty were significantly decreased; except for reduction of sperm motility (p< 0.01), the other effects were not observed in the offspring of experimental group ІІ. In summary, our data show that prenatal exposure of male rat fetuses to excess testosterone disrupted reproductive function, an effect highly dependent on the time, duration and level of exposure. It seems that the reproductive system in individuals exposed to high levels of androgens during fetal life should be evaluated at puberty and likely to be treated.